Long-term monitoring muscular enzymes in football players - Mercuri, R.; Stefani, L.; Innocenti, G.; Moretti, A.; Manetti, P.; Galanti, G. (Archivos de medicina del deporte, 2008)
Introduction: The skeletal muscle enzymes level is a marker of the functional status of muscle tissue, and varies widely in both pathological and physiological conditions. An increase in these enzymes may be an index of cellular and tissue damage as a consequence of acute or chronic muscle injuries. However changes in serum levels of muscular enzymes are also found in normal subjects and athletes after strenuous exercise and the amount of enzymes release from muscle tissue into blood can be infl uenced by physical exercise. The aim of study is to evaluate and follow up in football players the muscular enzyme plasma levels 24 h after every offi cial match for almost two months. Methods: Since September 2007 to November 2008 among the 18 professional footballers (7 defenders, 7 midfi elders and 4 forwards) of Serie A team ACF Fiorentina a consecutive blood sample was obtained. Plasma creatine kinase (CK), myoglobin (Mb) and lactated dehydrogenase (LDH) activity were determined exclusively in subjects playing a match, 24 h after a official match. Results: The values are expressed as mean as standard deviation. The day after the match, the plasma levels of CK, Mg and LDH was signifi cantly higher than at rest (CK 748 U/L , Mg 91 ng/mL and LDH 224 U/L). In addition CK shows values within the range from 156 to a maximum 1953 U/L. Mg a range from 36 to 318 ng/mL and LDH from 166 to 255 U/L. A signifi cant correlation is present between CPK and Mg values (r=0.86) Conclusions: The data shows that a series soccer- matches determines an increase in the muscular enzyme plasma levels. The behaviour of them after a strenuous exercise is peculiar for each athlete that has personal values of references. There are numerous factors and variability in a match that can modify the enzyme level: among these the number of contrast and injuries, the emotive and physical intensity of the competition and the ambient temperature. For further clinical implication several studies will be necessary in future.